A DHT-based approach for path selection and message forwarding in IEEE 802.11s industrial wireless mesh networks - Marcos Pinheiro (2009)
Wireless Mesh Networks (WMNs) are a promising communication technology that may offer greater flexibility and reliability, when compared to traditional wireless networks. WMNs open up new applications domains, but still need to find efficient mechanisms to deal with scalability and timeliness requirements. This paper proposes a scheme for Path Selection and Message Forwarding in IEEE 802.11s networks, that is suitable to be used in industrial environments. We present the DHT-based Cluster Routing Protocol (DCRP), a routing protocol based on DHTs, clustering of nodes and use of proxies. DCRP allows to improve the overall network performance by reducing the time required for path selection and the number of communication hops in large sized networks.